Analisis website perpustakaan digital kenukliran menggunakan goolge search console dan google analytics - Noeraida; Heru Tamtomo; Anggiana Rohandi Yusuf (Jurnal Pustakawan Indonesia, 2022)
Introduction. Digital library websites are currently the most widely used to find the information and literature, because they are more accessible and not limited by space and time. For optimally used, an evaluation must be carried out by analyzing the performance and characteristics of website visitors. This study aim to analyze website performance and the features of visitors to the nuclear digital library. Method. The study used a descriptive research method. Population is website visitors on the https://digilib.batan.go.id/ site from March-December 2021, as many as 3,293 people. The data collection technique from Google Search Console (GSC) and Google Analytics (GA). Findings. The results showed that the average website performance on search engines was 10.6. The highest keyword-based search is dosimetry 295. The top page with the most clicks is the article published in the proceedings. Indonesia is the country with the most broadcasts out of 227 countries. The characteristics of website visitors have increased with a total of 3,923 visitors. The demographics of website visitors, Indonesia occupied the highest position, and the highest cities is Jakarta. The highest browser usage is chrome at 81.21%, windows operating system 75.84% and desktop devices at 82.21%. Conclusion. Website performance has increased after adding GSC. Similarly, the characteristics of website visitors from GA data have increased, but decreased in the following month. In order for the number of visitors to continue to increase, the website content must always increase.